Optimism and Mental Health of Minority Students: Moderating Effects of Cultural Adaptability - Chen, Yongyong; Su, Jing; Ren, Zirong; Huo, Yongquan (Frontiers in Psychology, 2019)
This questionnaire study assessed the optimism, cultural adaptability, and mental health mechanisms of 1027 Tibetan undergraduates in China. The results of path analysis showed that, first, cultural adaptability played a positive role in moderating the relationship between optimistic trend and depressed self-efficac. Second, cultural adaptability was not a significant moderator of the relationship between optimism and anxiety. Third, cultural adaptability coordinated the relationship between optimistic self-efficacy and life satisfaction.